1976
DOI: 10.1107/s0567740876007267
|View full text |Cite
|
Sign up to set email alerts
|

The crystal and molecular structure of the enol form of 1-phenyl-1,3-butanedione (benzoylacetone) by neutron diffraction

Abstract: The crystal structure of the enol form of 1-phenyl-l,3-butanedione, Cl0H10Oz, has been determined from three-dimensional, neutron-diffraction data. The structure was refined by full-matrix least-squares methods to an R of 0.098 (0.046 for reflexions with I>_ 2"3o-i) and wR of 0.049 (0.042) for 1184 reflexions.The short, intramolecular O. • • O contact is 2.489 (5) A,. The hydrogen bond is slightly asymmetric but, because of large thermal motion, the asymmetry is of doubtful significance. From the bond lengths … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Again, we expect that in the gas phase at room temperature the system is more symmetric due to thermal fluctuations; Gilli et al concluded that it was a low-barrier, asymmetric, double-well system. We note in passing that a double well may arise not only when the reaction coordinate is along the bond but also when it is the bond angle. , …”
mentioning
confidence: 90%
See 2 more Smart Citations
“…Again, we expect that in the gas phase at room temperature the system is more symmetric due to thermal fluctuations; Gilli et al concluded that it was a low-barrier, asymmetric, double-well system. We note in passing that a double well may arise not only when the reaction coordinate is along the bond but also when it is the bond angle. , …”
mentioning
confidence: 90%
“…We note in passing that a double well may arise not only when the reaction coordinate is along the bond but also when it is the bond angle. 29,30 Most of these calculations or interpretations of experimental data of gas phase molecules did not address quantum nuclear effects (QNEs), which derive from the delocalized wave function of the proton. However, Tuckerman et al, 31 in a theoretical study pointed out that not only is the quantum nature of the proton relevant but also that of the heavy atoms in a molecule such as malonaldehyde.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(7) 1.0114 (8) Keto-Enol tautomerism of 1,3-diketones such as bzac has been extensively studied [14]. Neutron diffraction and accurate low temperature X-ray diffraction reveals that within the conjugated enol ring of bzac the C-C bond furthest from the phenyl ring is slightly longer than the C-C bond nearest the phenyl ring [15,16]. The relatively longer C(15)-C(16) bond [1.404(4) Å ] and shorter C(14)-C(15) bond [1.388(4) Å ] in the structure agree well with the above conclusion.…”
Section: Crystal Structurementioning
confidence: 99%
“…1. Final atomic coordinates for the non-hydrogen atoms are listed in Table 1 and interatomic bond lengths and valency angles are in Table 2 (5) 4649 (1) 666 -1822 (8) 4284 (3) 929 -1428 (7) 2047 (2) 675 4590 (5) 4377 (1) 751 11169 (4) 3283 (1) 672 7495 (4) 5171 (1) 654 (Jones, 1976b) and 1,3-diphenyl-1,3-propanedione (III) (Jones, 1976a Jeffrey & Takagi (1978) have suggested that, in order to compare X-ray and neutron diffraction data, the O-H bond lengths of X-ray studies should be normalized to 0.97/k. Contraction of the O(15)-H(15) bond results in parameters that make the asymmetry of (I) appear even more marked.…”
mentioning
confidence: 99%